Managing drug shortages in pediatric care - Rosário, Alexandra; Hankó, Balázs; Zelkó, Romána (Frontiers in Pharmacology, 2024)
The global impact of drug shortages on healthcare systems is a concerning issue that needs urgent attention. These shortages not only jeopardize patient care, public health, and healthcare delivery but also pose distinct challenges for pediatric populations due to their specific medication requirements and vulnerabilities. It is imperative to address this issue to safeguard the health and well-being of this specific age group. This review Gaimed to conduct a systematic analysis of strategies for addressing drug shortages in pediatric care from 2014 to 2024. The search included five databases: PubMed, Reaxys, Embase, Scopus, and Science Direct, using the keywords "drug shortage" and "pediatric". The final protocol was developed following the guidelines outlined in the " The PRISMA 2020 statement: An updated guideline for reporting systematic reviews". In total, 234 publications were identified. After screening the search results and applying inclusion and exclusion measures, a total of 27 original research papers were included. The primary finding indicates that a comprehensive approach rooted in risk management can significantly mitigate drug shortages in pediatric settings. This approach should address underlying causes such as manufacturer and delivery challenges and focus on prevention through enhanced forecasting and vigilant shortage monitoring. The most prevalent response involved seeking alternative treatment options. It is imperative to implement institutional and national guidelines, foster communication, and provider education, and minimize waste to effectively mitigate drug shortages in pediatric settings.